PEMANFAATAN SERAT BAMBU SEBAGAI BAHAN TAMBAH CAMPURAN BETON - Mulyati, Mulyati; Arman, Arman; Aulia Farhan , Muhammad; Alawiyah, Nurfelia (Jurnal Teknologi dan Vokasi, 2024)
Bamboo is a fiber-producing plant that can be used as an alternative fiber additive for concrete mixes to overcome cracks in concrete. The aim of this research is to determine the compressive strength and split tensile strength values of concrete from the use of bamboo fiber as an additional ingredient in the concrete mixture. The bamboo used is petung bamboo and apus bamboo, the fiber size is 20 mm long and 1-2 mm in diameter, with a percentage of 1%, 2%, 3%, 4%, 5% of the cement weight. Concrete mix planning uses SNI 7656-2012 for a planned compressive strength of 20 MPa at 28 days. The results of testing the compressive strength and split tensile strength of concrete from the percentage of use and, for petung bamboo, the average concrete compressive strength was respectively 23.58 MPa, 24.69 MPa, 19.45 MPa, 17.17 MPa, 13.02 MPa, and the split tensile strength of concrete were respectively 2.05 MPa, 2.40 MPa, 2.06 MPa, 2.03 MPa, 2.02 MPa, while for apus bamboo the average concrete compressive strength was obtained respectively 22.56 MPa, 23.07 MPa, 15.37 MPa, 14.09 MPa, 14.07 MPa, and the average splitting tensile strength of concrete is 2.15 MPa, 2.50 MPa, 2.47 MPa, 2.40 MPa. Using of up to 2% bamboo fiber in the concrete mixture can increase the compressive strength of the concrete, and using up to 5% bamboo fiber can increase the split tensile strength of the concrete. Petung bamboo fiber produces a higher compressive strength of concrete than apus bamboo fiber, while apus bamboo fiber produces a higher split tensile strength of concrete than petung bamboo fiber